University dropouts and labor market success - Sylke V. Schnepf (IZA World of Labor, 2015)
With university education continuing to expand worldwide, university dropouts will make up a large group in future labor markets. Dropping out is routinely viewed as a negative indicator. However, data on university dropouts does not generally provide information on their labor market outcomes, so empirical evidence is sparse. The studies that have examined the issue show that dropping out can be more of an advantage than not having enrolled in university at all. Many dropouts are more likely than upper secondary school graduates with no university education to progress in their careers. And many graduate later in their life.
Keywords: I21; 330; higher education; dropout; labor market chances; international comparison